Digital Technologies in Wholesaling and Retailing - Weber, F. (Encyclopedia of Organizational Knowledge, Administration, and Technology, 2020)
The ever increasing intra- and inter-competition, increased costs and a lower differentiation margin have led to intense competitive pressures within the domains of wholesaling and retailing. At the same time the increasing digitization due to technological innovation will radical change the economical and procedural fundamentals. In addition, from an entrepreneurial point of view, it must also be considered that the complexity of decision-relevant framework conditions has increased. Digitalisation is therefore to be seen as an essential driver for optimising business processes and as the basis for a new understanding of products and services. However, it cannot be considered independently of other social trends. The chapter will elaborate the underlying drivers and technological trends empowering the transformation processes within the domain of wholesaling and reailing. Starting from these major drivers we will scrutinize the impact of technological advancements and the opportunities, risks and constraints which are connected with it.